A Cross-Sectional analysis of factors affecting teacher’s work performance in China - Chen, Yueqin; Mohammed, Lubna Ali (Journal of Ecohumanism, 2024)
China is a country renowned for its robust education system and one with the best education system in the world particularly in STEM education as reported by international assessments entities like PISA. The country is also known for adopting teachers’ centric education framework and recognizing their crucial role in shaping talents within the education system. Despite these, teachers face several obstacles while discharging their duties. These includes intense competition and pressure within the system which can result in student stress and neglect of holistic development. This study aims to explore challenges faced by teachers within the education system by both primary quantitative and secondary methods. It focuses on the influence of principal leadership, work culture and teacher motivation on teacher performance in Chinese schools which were found to have significant influence of performance. This provide guidance and suggestions for improving the quality of education in China.